The effects of aerobic exercise on goal-directed attention and inhibitory control in individuals with high trait anxiety: an EEG study - Mengyang He; Jinxia Guo; Shunyao Yu; Hao Lian; Ruijie Zhan; Rongrong Luo; Zhifei Shi; Zhidong Zhuang; Wenpeng Cai (BMC Psychology)
Abstract Anxiety is known to significantly impair cognitive function, particularly attentional control. While exercise has been demonstrated to alleviate these cognitive deficits, the precise neural mechanisms underlying these effects remain poorly understood. This study examines the effects of exercise on attentional control in individuals with high trait anxiety, based on attentional control theory, which suggests that such individuals have reduced top-down attention. Thirty-eight participants were randomly assigned to either an exercise group or a reading group. The exercise group engaged in 30 min of moderate-intensity cycling, while the reading group spent 30 min reading quietly. In Experiment 1, goal-directed attention was assessed using a cue-object paradigm, and in Experiment 2, inhibitory control was evaluated through a visual search task. EEG data indicated that the exercise group exhibited significantly larger Pd components in both experiments, suggesting enhanced attentional focus and improved inhibition of distractors. These findings suggest that aerobic exercise enhances top-down attentional processes, particularly goal-directed attention and distractor inhibition, offering potential as an intervention for individuals with high trait anxiety.